POLA KOMUNIKASI ORANG TUA TERHADAP ANAK PECANDU GAME ONLINE DI KELURAHAN PAYAGELI KECAMATAN SUNGGAL KABUPATEN DELI SERDANG - cut umairah cut umairah (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2022)
The development of science and technology along with the increasingly rapid development of the era turned out to bring changes in all walks of life, internet users are no longer always associated with work but rather towards playing online games. negative effects, such as the effect of opium for fans. The assessment method used in this research is a qualitative approach. While this type of research uses a qualitative description, where the researcher describes with in-depth interviews of the research object. The research method is a benchmark in studying the rules contained in research and from the philosophical point of view of the research methodology is the epistemology of research on parental communication patterns controlling children's desires with the motivation of children's desires, but with a warm attitude, there is reciprocal communication between parents and children. children who do it rationally, tell positive and negative things, want to listen to children's complaints and feelings, so that children want to express what they feel, parents are friendly The communication patterns of parents with teenagers in internet media dependence are shown by various communication patterns, namely permissive , and authoritative. Communication barriers between parents and teenagers due to lack of time to meet with children, parents' busyness with their work makes parents easily angry because they are tired after work..